Pedasaran Filsafat Hak Asasi Manusia Menurut Höffe and Lohmann - Otto Gusti Ndegong Madung; Adrianus Yohanes Mai; Winibaldus Stefanus Mere (Jurnal HAM, 2025)
This article aims to philosophically justify the universality and the existence of human rights. Historically, the concept of human rights has evolved according to the context in which human rights are lived. One of the themes of debate is how human rights are justified or validated and how they can be universally accepted. Philosphers always have different opinions about what constitutes the basis of human rights. This article considers Höffe and Lohmann who sepciafically address this problem. Based on the philosophical approaches of Otfried Höffe and Georg Lohmann, this research emphasizes the universal validity of human rights. On the one hand, Otfried Höffe justifies the necessity of human rights in his anthropological approach of "transcendental exchange" which is the conditions for the possibility of being human. These conditions concern humans as physical and living beings, as linguistic and rational beings, and as social and cooperative beings who have transcendent interests in their lives. On the other hand, Georg Lohmann grounds human rights through a mutual moral obligation to recognize others as equal subjects.  Moral obligation arises from a person's ability to decide what is good or bad. Both Höffe and Lohmann ground human rights on reciprocity. In analyzing both views of human rights, qualitative method is used in this research which focuses on literature study. This research finds that the universal nature of human rights is grounded in human vulnerability, reciprocity of mutual respect, and integration of moral obligations into legal frameworks for the protection of self-determination and dignity.